Dynamic Guaranteed Cost Event-Triggered-Based Anti-Disturbance Control of T-S Fuzzy Wind-Turbine Systems Subject to External Disturbances - Gu, Yang; Shen, Mouquan; Park, Ju H.; Wang, Qing-Guo; Zhu, Zheng Hong (IEEE transactions on fuzzy systems, 2024)
In this article, we investigate an improved dynamic guaranteed cost event-triggered-based anti-disturbance control for Takagi-Sugeno fuzzy wind-turbine systems subject to external disturbances. A guaranteed cost event-triggered paradigm with dynamic threshold and sector structure is constructed to alleviate unnecessary triggers caused by outlier measurement. An additional event condition is designed to deal with the difference of premise variable between the system and controller. A PI-type intermediate estimator is introduced to simultaneously estimate the system state and external disturbance. Subsequently, an event-triggered fuzzy controller is built to actively compensate the external disturbances. With the help of Finsler's lemma, sufficient criteria are derived in terms of linear matrix inequalities to make the wind-turbine systems asymptotically stable. Finally, the proposed method is verified by comparative studies.